Peningkatan Pemahaman Warga Tundan, RT 04, Kalurahan Tamantirto mengenai Dampak Negatif dari Pernikahan di Bawah Umur - Istianah Zainal Asyiqin; Ani Yunita; Muhammad Habibi Miftakhul Marwa (Jurnal Surya Masyarakat, 2024)
Residents of Tundan, RT 04, Tamantirto, Kasihan, Bantul still often marry their sons and daughters under the age of 19 due to various considerations, for example, the bride who must be married immediately or because of the strong will of the parents. This service aims to solve the problem of underage marriage so that an intensive study is carried out in the form of material presentation, analysis, discussion, and case studies on the negative impacts of underage marriage. The method applied in this community service program is to organize studies and discussions at partner locations in Tundan, RT 04, Tamantirto, with 52 participants. Based on the results of the pre-test and post-test, the participants experienced an increased understanding of Law Number 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning marriage by 50%, an increased understanding of the minimum age for marriage by 25%, an increased understanding of the factors that cause underage marriages by 26%, understanding of the negative impact of underage marriages has increased by 21%, and increased understanding of legal procedures that must be followed if underage marriages are forced to be carried out by 40%. Hopefully, this increased understanding can suppress underage marriage.